The Role of Remuneration Contribution and Social Support in Organizational Life to Build Work Engagement - fauchil, Fauchil Werdati; Didit, Didit Darmawan; Nikmah, Nikmah Rochmatin Solihah (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2020)
The increasingly diverse levels of human needs along with the high intensity causes them to need regular income in a large amount. These demands can make someone change work to earn a higher income. For companies, the phenomenon of employees who often changes work becomes a problem because of the high intensity of employee turnover can affect company productivity. The human resources department needs to learn more specifically about employee work engagement to prevent employees from leaving a job. The growing sense of employee engagement can be supported by many factors. This study aims to analyze and find out and describe the effects of remuneration and social support on work engagement. The population in this study were all employees of PT Mega Multi Spring with 80 respondents taken based on a purposive sampling technique. This study uses primary data in the form of respondents' responses to variables using a questionnaire. The analytical tool used is linear regression. The results showed that remuneration had a significant positive effect on work engagement. In addition it was also found that social support had a significantly positive effect on work engagement. In the end remuneration and social support variables have a significant simultaneous effect on work engagement. From the results of the study it can be concluded that proper remuneration and positive social support make employees have a sense of attachment to work.